The Influence of Financial Ratios, Sukuk Structure and Corporate Governance on Sukuk Ratings - Dwitami, Yuska Supra; Suryanto, Tulus; Noviarita, Heni; Anggraeni, Erike (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
This study aims to determine the effect of financial ratios, Sukuk structure, and corporate governance on the rankings of Sukuk issued by companies listed on the Sharia Securities List for the period 2014-2018. This study uses secondary data, namely financial reports and annual reports of companies listed in the 2014-2018 Sharia Securities List, Sukuk ranking data from the website of PT. PEFINDO and data on Sukuk were still circulating during the year of observation from the website of the financial services authority. A total of 34 Sukuk issued by companies listed on the Sharia Securities List during the study period became the population in this study. The sample obtained was 15 Sukuk during 5 years of observation, so that the final sample was obtained as many as 75 observation data. The research results prove that only the profitability ratio variable influences the Sukuk rating. Meanwhile, other variables, namely liquidity ratio, leverage ratio, activity ratio, Sukuk structure, and corporate governance, do not influence the Sukuk rating